2021
DOI: 10.3390/fermentation7020073
|View full text |Cite
|
Sign up to set email alerts
|

LC-ESI-QTOF-MS/MS Characterisation of Phenolics in Herbal Tea Infusion and Their Antioxidant Potential

Abstract: Ginger (Zingiber officinale R.), lemon (Citrus limon L.) and mint (Mentha sp.) are commonly consumed medicinal plants that have been of interest due to their health benefits and purported antioxidant capacities. This study was conducted on the premise that no previous study has been performed to elucidate the antioxidant and phenolic profile of the ginger, lemon and mint herbal tea infusion (GLMT). The aim of the study was to investigate and characterise the phenolic contents of ginger, lemon, mint and GLMT, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 101 publications
(127 reference statements)
0
28
3
Order By: Relevance
“…Caffeic acid, previously identified in tamarind seeds by El-Haddad et al [42], was also identified in all three samples. Furthermore, cinnamic acid (previously identified in star anise [30]) was identified in mountain pepper and tamarind (Figure S2), and ferulic acid was detected in mountain pepper and finger lime (Figure S2). These phenolics have been specifically highlighted as they are recognized for their medicinal properties [43,44].…”
Section: Phenolic Acidsmentioning
confidence: 79%
See 1 more Smart Citation
“…Caffeic acid, previously identified in tamarind seeds by El-Haddad et al [42], was also identified in all three samples. Furthermore, cinnamic acid (previously identified in star anise [30]) was identified in mountain pepper and tamarind (Figure S2), and ferulic acid was detected in mountain pepper and finger lime (Figure S2). These phenolics have been specifically highlighted as they are recognized for their medicinal properties [43,44].…”
Section: Phenolic Acidsmentioning
confidence: 79%
“…Then, 25 μL of 10% Na 2 CO 3 was added and the absorbance at 765 nm was recorded after 1 h. Gallic acid (0–200 μg/mL) was used to generate the standard curve for the quantification of TPC. DPPH (modified from Chou et al [ 30 ]) and ABTS (described by Bashmil et al [ 31 ]) assays must be conducted in the dark (presence of red light). For DPPH, 275 μL (0.1 mM DPPH) and 25 μL sample or standard were mixed and incubated for 30 min in the dark before spectrophotometer reading at 517 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Quercetin 3′- O -glucuronide (compound 47 —477.0676) and quercetin 3- O -arabinoside (compound 50 —433.0783) were formed the fragment ions at m / z 301 via the subtraction of one unit of glucuronide (176 Da) and one unit of C 5 H 8 O 4 (132 Da) from the precursor ions, respectively. Previously, these were reported in mint and lemon with strong antioxidant potential [ 38 , 39 ]. The compound 52 (3,7-Dimethylquercetin—C 17 H 14 O 7 ) was detected in basil, mint, oregano, rosemary and sage in positive and negative modes, which produced daughter ions at m / z 314, 299, 217 through the removal of CH 3 , 2CH 3 and two CH 3 plus one unit of CO [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The method of Tang, et al [39] and Chou, et al [40] with some changes was used to quantify polyphenols in banana extracts. This was accomplished using a Water Alliance (2690) HPLC coupled with photo array detector (PDA).…”
Section: Quantification Of Bananas' Phenolics By Hplc-pdamentioning
confidence: 99%